Factors Affecting Construction Labour Productivity using Questionnaire Survey - Madhan, A; G I, Gunarani (International Journal of Engineering and Technology, 2018)
Theoretically the most difficult issue in development industry is to enhance the production efficiency. Numerous researches have been done previously, however a more profound comprehension is as yet expected to enhance the labour productivity. The fundamental result from the writing is that there is no standard definition for labour work profitability. It covers the development labour productivity definitions, angles and factors influencing it. The labour productivity is particularly essential in developing countries, where the vast most of the building development work is still on manual premise. The point of this investigation is to get the most recent data and to recognize the key factors that influence the labour work efficiency in and around Thanjavur. So overview is brought out through questionnaire surveys and circulate to respondents who work at different undertakings in wide region in Thanjavur and the poll are evaluated by venture supervisors, project managers, construction engineers, field workers and furthermore with works utilizing their experience. What's more, the information's are gathered and investigated utilizing Relative Important Index (RII) and Importance Index (IMPI) methods, utilizing this the influenced factors are distinguished and positioned, through the vital advances are given to enhance the work efficiency.Â Â
Keywords: Construction work efficiency; Factors influencing labour productivity; Questionnaire review; Improve labour productivity.